109k views
21 votes
If h=5 what is 2 x (6-h



User Jscul
by
4.9k points

2 Answers

9 votes

Answer:

Explanation:

Equation : 2 × (6 - h)

Because h = 5, replace the variable h with 5.

2 × (6 - 5)

Solve the equation in the parentheses.

6 - 5 = 1

The equation is now 2 × 1, which is equal to 2.

So, 2 × (6 - h) is 2.

Hope this helped !

User Geschema
by
4.7k points
1 vote
Substitute:
So 2 x (6-5)
Do everything in the brackets:
6 - 5 = 1
Then 2 x 1 = 2
Therefore the answer is 2
User Nicosantangelo
by
5.0k points